A multifaceted evaluation of microgliosis and differential cellular dysregulation of mammalian target of rapamycin signaling in neuronopathic Gaucher disease - Zhang, Zhenting; Wang, Xiaohong; Lin, Yi; Pan, Dao (Frontiers in Molecular Neuroscience, 2022)
Neuronopathic Gaucher disease (nGD) is an inherited neurodegenerative disease caused by mutations in GBA1 gene and is associated with premature death. Neuroinflammation plays a critical role in disease pathogenesis which is characterized by microgliosis, reactive astrocytosis and neuron loss, although molecular mechanisms leading to neuroinflammation are not well-understood. In the present Brief Report, we developed an convenient tool to evaluate microglia proliferation and activation independently and uncovered abnormal proliferation of microglia by 2-fold in an adult genetic nGD model, i.e., 4L;C* mice. The nGD-associated pattern of inflammatory mediators pertinent to microglia phenotypes was determined, showing a unique signature favoring pro-inflammatory chemokines and cytokines. Moreover, highly polarized (up or down) dysregulations of mTORC1 signaling with varying lysosome dysfunctions (numbers and volume) were observed among three major cell types of nGD brain. Specifically, hyperactive mTORC1 signaling was detected in all disease-associate microglia (Iba1high) with concurrent increase of lysosome function. Conversely, mTORC1 hypoactivity was implicated in neurons (including Purkinje-like cells) which were accompanied by inconsistent changes of lysosome function in nGD mice. Undetectable levels of mTORC1 activity and low Lamp1 puncta were noticed in astrocytes of both diseased and normal mice, suggesting a minor involvement of mTORC1 pathway and lysosome function in disease-associate astrocytes. These findings highlight the differences and complexity of molecular mechanisms that are involved within various cell types of brain. The quantifiable parameters established and nGD-associated pattern of neuroinflammatory mediators identified would facilitate the efficacy evaluation on microgliosis and further discovery of novel therapeutic target(s) in treating neuronopathic Gaucher disease.